Saudi Female International College Students’ Self-Identities Through the Use of Social Media in the United States - Alruwaili , Tahani; Ku, Heng-Yu (Journal of International Students, 2020)
This study explored 14 Saudi female international college students’ self-identities through social media use while they were studying in the United States. Data was collected by semistructured interviews. In addition, participants were asked to draw pictures that represented how they experience social media use in Saudi Arabia and in the United States as part of the interviews. The findings revealed that many participants indicated they experienced some changes to their identities after coming to the United States. Many of the participants expressed they were more open and more independent after coming to the United States. They felt they could express their identities on social media to a greater degree and enjoyed using it to connect with others. Although most of the participants became more comfortable with interaction and expression on social media in the United States, many of them still retained some measures to ensure their privacy.